Regular inhaled corticosteroids in adult-onset asthma and the risk for future cancer: a population-based cohort study with proper person-time analysis - Kok VC; Horng JT; Huang HK; Chao TM; Hong YF (Dove Medical Press, 2015)
Victor C Kok,1,2 Jorng-Tzong Horng,2,3 Hsu-Kai Huang,3 Tsung-Ming Chao,4 Ya-Fang Hong5 1Division of Medical Oncology, Department of Internal Medicine, Kuang Tien General Hospital, Taichung, Taiwan; 2Department of Biomedical Informatics, Asia University Taiwan, Taichung, Taiwan; 3Department of Computer Science and Information Engineering, National Central University, Jhongli, Taiwan; 4Statistics Unit, Department of Applied Geomatics, Chien Hsin University, Jhongli, Taiwan; 5Institute of Molecular Biology, Academia Sinica, Nankang, Taipei, Taiwan Background: Recent studies have shown that inhaled corticosteroids (ICS) can exert anti-inflammatory effects for chronic airway diseases, and several observational studies suggest that they play a role as cancer chemopreventive agents, particularly against lung cancer. We aimed to examine whether regular ICS use was associated with a reduced risk for future malignancy in patients with newly diagnosed adult-onset asthma. Methods: We used a population-based cohort study between 2001 and 2008 with appropriate person-time analysis. Participants were followed up until the first incident of cancer, death, or to the end of 2008. The Cox model was used to derive an adjusted hazard ratio (aHR) for cancer development. Kaplan–Meier cancer-free survival curves of two groups were compared. Results: The exposed group of 2,117 regular ICS users and the nonexposed group of 17,732 non-ICS users were assembled. After 7,365 (mean, 3.5 years; standard deviation 2.1) and 73,789 (mean, 4.1 years; standard deviation 2.4) person-years of follow-up for the ICS users and the comparator group of non-ICS users, respectively, the aHR for overall cancer was nonsignificantly elevated at 1.33 with 95% confidence interval (CI), 1.00–1.76, P=0.0501. The Kaplan–Meier curves for overall cancer-free proportions of both groups were not significant (log-rank, P=0.065). Synergistic interaction of concurrent presence of regular ICS use was conducted using “ICS-negative and chronic obstructive pulmonary disease (COPD)-negative” as the reference. The aHR for the group of “ICS-positive, COPD-negative” did not reach statistically significant levels with aHR at 1.38 (95% CI, 0.53–3.56). There was a statistically significant synergistic interaction of concurrent presence of regular ICS use and COPD with aHR at 3.78 (95% CI, 2.10–6.81). Conclusion: The protective effect of regular ICS use in the studied East Asian patients with adult-onset asthma was not detectable, contrary to reports of previous studies that ICS might prevent the occurrence of future cancer. Keywords: immortal time bias, NHIRD, population-based study, retrospective cohort study, risk of cancer